The impact of ownership structure on corporate debt policy of banking industry in Malaysia - Wong, Siik Ching (Universiti Malaysia Sarawak (UNIMAS), 2012)
This study was conducted to investigate the impact of ownership structure on corporate debt policy of banking industry in Malaysia. It also identifies the detenninants of the ownership structure in banking Malaysia. 8 local banks which are listed in Bursa Malaysia between 2005 and 20 I 0 were selected as the sample of the study. A pooled Ordinary Least Square COLS) analysis was used to examine the relationship between ownership structure and corporate debt policy in banking Malaysia. The findings indicate that there is an insignificant relationship between profitability and debt ratio. However, the results find that finn size, growth opportunity,.'and institutional ownership have a positive and significant relationship with the debt ratio. In contrast, the firm risk and managerial ownership have a significant and negative effect on the debt ratio. These findings are consistent with the pecking order theory and agency theory. Hence, the corporate debt policy can be used as a mechanism to mitigate the agency conflict in banking Malaysia.